Stanislavsky and yoga - Cherkasskii, Sergei (Icarus Publishing Enterprise ; Routledge, 2016)
This book deals with one of the most important sources of the Stanislavsky System - Yoga, its practice and philosophy. Sergei Tcherkasski carefully collects records on Yoga in Stanislavsky's writings from different periods and discusses hidden references which are not explained by Stanislavsky himself due to the censorship in his day. Vivid examples of Yoga based training from the rehearsal practice of the Moscow Art Theatre and many of Stanislavsky's studios (the First Studio in 1910s, the Second Studio and Opera Studio of the Bolshoi Theatre in 1920s, Opera-Dramatic Studio in 1930s) are provided. The focus of Tcherkasski's research consists of a comparative reading of the Stanislavsky System and Yogi Ramacharaka's books, which were a main source for Stanislavsky. Accordingly, Tcherkasski analyzes elements of the System based on Yoga principles.